Acute physical exercise increases the adaptor protein APPL1 in the hypothalamus of obese mice - Gaspar, Rafael Calais; Muñoz, Vitor Rosetto; Formigari, Guilherme Pedron; Kuga, Gabriel Keine [UNESP]; Nakandakari, Susana Castelo Branco Ramos; Botezelli, José Diego; da Silva, Adelino S.R.; Cintra, Dennys Esper; de Moura, Leandro Pereira [UNESP]; Ropelle, Eduardo Rochete; Pauli, José Rodrigo (Elsevier, 2018)
Adiponectin is considered an adipokine that has essential anti-inflammatory and insulin-sensitivity actions. The adaptor protein containing the pleckstrin homology domain, the phosphotyrosine-binding domain, and leucine zipper motif 1 (APPL1) is a protein involved in adiponectin signaling that plays a role in many physiological and pathophysiological processes. In the central nervous system, adiponectin can potentiate the effects of leptin in the arcuate proopiomelanocortin (POMC) neurons. However, the role of APPL1 in the hypothalamus is not well understood. Therefore, in this study, we explored the effects of acute physical exercise on APPL1 protein content in the hypothalamus and food intake control in leptin stimulated-obese mice. Here we show that acute exercise increased serum adiponectin levels and APPL1 content in the hypothalamus, which were followed by reduced food intake in obese mice. Further, at the molecular level, the exercised obese mice increased the protein kinase B (Akt) signaling in the hypothalamus and attenuated the mammalian homolog of Drosophila tribbles protein 3 (TRB3) levels. In conclusion, the results indicate physical exercise is capable of increasing APPL1 protein content in the hypothalamus of leptin stimulated-obese mice and modulating food intake.
Keywords: Adiponectin; APPL1; Hypothalamus; Obesity; Physical exercise